Effects of Temperature and Defoliation Frequency on Dry Matter Production and Nutritive Value of Imperata Cylindrica - Muhammad Rusdy (Faculty of Animal Science, Universitas Gadjah Mada, 2006)
File lengkap ada dalam bentuk PDF dibawah ini